Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Dinas Pendidikan Kota Depok - Intan Firliyani; Nariah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of work discipline and work motivation on employee performance at the Depok City Education Office. The type of research used is quantitative research. Data collection was carried out by utilizing the research instruments used, the data analysis used was quantitative/measurable with the aim of testing previously established hypotheses. In this study, the samples were 58 employees at the Depok City Education Office. The regression equation concludes that there is an influence between X1 and Y. The correlation coefficient is 0.787, meaning that the two variables have a strong level of influence. Thus, H01 is rejected and Ha1 is accepted, this shows that there is a partially significant influence between X1 and Y. That variable X2 influences variable Y by 78.9% while the remaining 21.1% is influenced by other factors. Thus, H02 is rejected and Ha2 is accepted, this shows that there is a partially significant influence between the level of relationship is very strong with Y. The R-Square value is 0.795, so it can be concluded that the variables of work discipline and work motivation influence employee performance variables by 79.5% while the remaining 20.5% is influenced by other factors.